2009
DOI: 10.1186/1477-5956-7-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of HIV-1 associated dementia: proteomic investigation of sera

Abstract: Background: New, more sensitive and specific biomarkers are needed to support other means of clinical diagnosis of neurodegenerative disorders. Proteomics technology is widely used in discovering new biomarkers. There are several difficulties with in-depth analysis of human plasma/ serum, including that there is no one proteomic platform that can offer complete identification of differences in proteomic profiles. Another set of problems is associated with heterogeneity of human samples in addition intrinsic va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 42 publications
2
60
0
Order By: Relevance
“…Additionally, as MDD is a complex mental disorder with poorly understood multifactorial aetiology, the individual variability cannot be excluded, although only firstonset, treatment-naive depressed patients were recruited in order to improve sample homogeneity. Dynamic measurement of potential biomarker levels for any given patient over time intervals may provide much more information than the evaluation of average levels (Wiederin et al 2009). However, this needs to be investigated in a longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, as MDD is a complex mental disorder with poorly understood multifactorial aetiology, the individual variability cannot be excluded, although only firstonset, treatment-naive depressed patients were recruited in order to improve sample homogeneity. Dynamic measurement of potential biomarker levels for any given patient over time intervals may provide much more information than the evaluation of average levels (Wiederin et al 2009). However, this needs to be investigated in a longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesised that this may be used to monitor the progress of HIV infection. Serum has also been used to search for biomarkers of HAND 12. Immunodepleted serum samples from patients with and without HAD were compared, and it was discovered that gelsolin and prealbumin were differentially expressed in these patient groups.…”
Section: Hiv Proteomic Researchmentioning
confidence: 99%
“…It has been reported that the compositions or functions of saliva will alter after infection [34]. Some differentially expressed proteins were identified in cerebrospinal fluid and sera for HIV-1 associated dementia [35,36]. However, changes of saliva proteins upon HIV-1 infection have not been profiled and identification of the differentially expressed proteins in HIV-1 seropositive patients is an important step in understanding effects of HIV-infection on human biofluids.…”
Section: Introductionmentioning
confidence: 99%